State repression and the labors of memory - Jelin, Elizabeth, 1941- (Contradictions (Minneapolis, Minn.), 2003)
Hearing the news from South America at the turn of the millennium can be like traveling in time: here are the trials of Pinochet, the searches for "the disappeared" in Argentina, the investigation of the death of former president Goulart in Brazil, the Peace Commission in Uruguay, the Archive of Terror in Paraguay, a Truth Commission in Peru. As societies struggle to come to terms with the past and with the vexing questions posed by ineradicable memories, this wise book offers guidance. Combining a concrete sense of present urgency and a theoretical understanding of social, political, and historical realities, State Repression and the Labors of Memory fashions tools for thinking about and analyzing the presences, silences, and meanings of the past.